Differential Responses of Eukaryotic Phytoplankton to Nitrogenous Nutrients in the North Pacific Subtropical Gyre - Rii, Yoshimi M.; Bidigare, Robert R.; Church, Matthew J. (Frontiers in Marine Science, 2018)
Fixed inorganic nitrogen (N) is persistently scarce in the well-lit regions of the subtropical ocean gyres and its supply plays an important role in controlling phytoplankton productivity. In a series of experiments conducted in the North Pacific Subtropical Gyre (NPSG), we examined changes in primary productivity and eukaryotic phytoplankton community structure in response to additions of nitrate (NO3-), ammonium (NH4+), or urea in conjunction with phosphate and silicic acid. Overall, we observed large increases in rates of 14C-primary productivity (~2- to 27-fold) and concentrations of chlorophyll a (~2- to 7-fold) following N addition. Much of the physiological response was due to larger (>3 µm) phytoplankton, whose contributions to primary productivity increased ~2-fold while picophytoplankton (0.2-3 µm) contributions decreased by a similar proportion. Five experiments, conducted in the spring, summer and winter, revealed apparent seasonally-dependent responses in phytoplankton community structure to N availability. During the summer, pennate diatoms increased significantly following N addition as evidenced by both photosynthetic pigment analyses and high-throughput sequencing of 18S rDNA. For example, following the addition of N substrates, concentrations of fucoxanthin (a diatom pigment biomarker) increased between 23- and 49-fold, and relative abundances of rRNA genes belonging to Pseudo-nitzschia increased from negligible (~0.3%) to 30-60% of the >3 µm phytoplankton assemblage. However, unlike the diatom-driven responses observed in the summer, experiments conducted in the spring and winter demonstrated large increases in concentrations of 19’-butanoyloxyfucoxanthin (a pelagophyte pigment biomarker) together with increases in the relative abundance of rRNA genes clustering among Pelagomonas. Overall, our findings revealed differences in the responses of major taxa during experiments conducted in different times of the year, with concomitant impacts on patterns of phytoplankton diversity. In addition, the overall responses in chlorophyll a, 14C-primary production, and eukaryotic phytoplankton community composition appeared largely independent of the type of N substrate added. Our results highlight seasonal-scale differences on the role of N availability in shaping eukaryotic phytoplankton diversity in the surface waters of the oligotrophic NPSG.